Acute physiological effects of whole body vibration (WBV) on central hemodynamics, muscle oxygenation and oxygen consumption in individuals with chronic spinal cord injury. (January 2014) - Yarar-Fisher, Ceren; Pascoe, David D.; Gladden, L. Bruce; Quindry, John C.; Hudson, Judith; Sefton, JoEllen
Abstract Purpose: (1) Investigate the acute effects of whole body vibration (WBV) on central hemodynamic responses, muscle oxygenation and oxygen consumption ( <![CDATA[\def\newpage{\vfill \break } \nopagenumbers $ \dot {\rm V} {\rm O}_2 $ \newpage \end]]> ) in individuals with spinal cord injury (SCI) versus sex, age and activity-matched able-bodied (AB) individuals. (2) Assess the effects of three WBV frequencies on all outcome measures. Methods: Eleven males with SCI and 10 AB individuals were recruited. Subjects completed three WBV exercise sessions at 30, 40 and 50 Hz. Heart rate (HR), mean arterial blood pressure (MAP), stroke volume (SV), cardiac output (CO), <![CDATA[\def\newpage{\vfill \break } \nopagenumbers $ \dot {\rm V} {\rm O}_2 $ \newpage \end]]> and relative changes in oxygenated (Δ[HbMbO2]), deoxygenated (Δ[HHbMb]) and total (Δ[HbMbtot]) heme groups were obtained when <![CDATA[\def\newpage{\vfill \break } \nopagenumbers $ \dot {\rm V} {\rm O}_2 $ \newpage \end]]> steady state was achieved for: pre-WBV sitting, pre-WBV standing, WBV and post-WBV standing. Results: Both groups demonstrated small but significant increases in <![CDATA[\def\newpage{\vfill \break } \nopagenumbers $ \dot {\rm V} {\rm O}_2 $ \newpage \end]]> , Δ[HbMbO2] and Δ[HbMbtot]; but the increases were larger in the SCI group. A significant decrease Δ[HHbMb] was observed in the SCI group. No frequency effect was observed. Conclusion: The WBV responses do not appear sufficient to induce cardiovascular benefits in the SCI population. WBV may be helpful for individuals with SCI in improving lower limb peripheral blood flow and coping with orthostatic hypotension symptoms earlier in their rehabilitation programs. Implications for Rehabilitation Increased muscle oxygenation and blood flow observations in response to WBV suggest a possible application of WBV for increasing lower extremity blood flow and/or oxygen saturation in individuals with SCI. WBV may be incorporated into the rehabilitation programs for reducing thrombosis susceptibility in individuals with SCI. Blood pressure in individuals with SCI appeared to be maintained much better in the upright position when WBV is applied. This could be helpful in the rehabilitation of SCI patients by allowing them to avoid the difficulties of orthostatic hypotension earlier in their rehabilitation programs.